2017
DOI: 10.1063/1.5007992
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the non-isothermal crystallization kinetics of polyamide 6 composites during thermoforming

Abstract: The combination of thermoforming processes of continuous-fiber reinforced thermoplastics and injection molding offers a high potential for cost-effective use in automobile mass production. During manufacturing, the thermoplastic laminates are initially heated up to a temperature above the melting point. This is followed by continuous cooling of the material during the forming process, which leads to crystallization under non-isothermal conditions. To account for phase change effects in thermoforming simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Earlier works on the crystallisation kinetics of polymers focused on isothermal DSC tests, where the sample is rapidly cooled from its melting to the crystallisation temperature and the heat that has evolved when the sample is held isothermal is measured. Isothermal crystallisation kinetics of glass-fibre-filled PA6 composites were studied in [22], which concluded that the addition of filler materials, such as fibres, influence the thermal properties of the polymers The analysis of the thermoforming process requires thermal properties of the organosheet material at process-relevant cooling rates in a range greater than 10 K/s, which is not possible using conventional differential scanning calorimeters, which are limited to a maximum of approximately 2.5 K/s [23]. In addition, while isothermal crystallisation is suitable for theoretical analysis, a manufacturing process performed under dynamic conditions should be investigated with non-isothermal crystallisation [24].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier works on the crystallisation kinetics of polymers focused on isothermal DSC tests, where the sample is rapidly cooled from its melting to the crystallisation temperature and the heat that has evolved when the sample is held isothermal is measured. Isothermal crystallisation kinetics of glass-fibre-filled PA6 composites were studied in [22], which concluded that the addition of filler materials, such as fibres, influence the thermal properties of the polymers The analysis of the thermoforming process requires thermal properties of the organosheet material at process-relevant cooling rates in a range greater than 10 K/s, which is not possible using conventional differential scanning calorimeters, which are limited to a maximum of approximately 2.5 K/s [23]. In addition, while isothermal crystallisation is suitable for theoretical analysis, a manufacturing process performed under dynamic conditions should be investigated with non-isothermal crystallisation [24].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…In addition, while isothermal crystallisation is suitable for theoretical analysis, a manufacturing process performed under dynamic conditions should be investigated with non-isothermal crystallisation [24]. Non-isothermal crystallisation kinetics of fibre-reinforced PA6 composites at high cooling rates were studied in [23] using extremely fast-operating calorimeters discussed in [17]. The shifting of the crystallisation peak to lower temperatures with increasing cooling rates was observed in [23].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 3 more Smart Citations